Analisis Pembuktian Alat Bukti Closed Circuit Television (CCTV) Sebagai Alat Bukti Petunjuk - William Abraham; Hery Firmansyah (Fakultas Hukum Universitas Tarumanagara, 2018)
Process of proofing is one of the most important in the trial. In the process of proofing, someone could be determined as defendant or not by relating the facts that happened with the available evidence in the trial. Process of proofing refers to Criminal Code Procedure Article 183 which about need minimum of 2 (two) valid evidence and to get Judge’s conviction and also refers to Criminal Code Procedure Article 184 which about valid evidence that can use in the trial. Along with the current development that continuously evolving, there is evidences outside of Criminal Code Procedure. Closed Circuit Television is one of many evidences that arranged in Law of Republic Indonesia Number 11 of 2008 concerning Information and Electronic Transaction. Now, Closed Circuit Television often used in trial to give more explanation about unclear facts to make it clear. But, to use Closed Circuit Television as evidence, it needs related to Criminal Code Procedure Article 188. To be able used as valid evidence Closed Circuit Television need to has correlation between facts in the trial and Closed Circuit Television itself